INCREASING TEACHERS' ABILITY USING ZOOM MEETING APPLICATIONS IN THE DISTANCE LEARNING PROCESS THROUGH COLLABORATIVE ASSISTANCE IN SD NEGERI BENDO KAPANEWON SAMIGALUH KULON PROGO ACADEMIC YEAR 2020/2021 - Francisca Saminem (Universitas Islam Indonesia, 2021)
This research was motivated by the regulation of the Ministry of Education and culture regarding the implementation of education during the Covid-19 pandemic which required distance learning using online learning media. Online learning is a learning method that aims to improve the ability of teachers to use the Zoom Meeting application program at SD Negeri Bendo Kapanewon, Samigaluh Kulon Progo during the Covid-19 pandemic. This research is a school action research to improve the ability of school principals in managing learning leadership through collaborative mentoring. The subjects in this study were SD Negeri Bendo teachers, totaling 8 teachers consisting of 6 classroom teachers and 2 subject teachers. The purpose of this study was to improve the ability of teachers in implementing distance learning by using the Zoom Meeting application for Bendo Elementary School teachers through collaborative mentoring activities. The results of preliminary observations show that the ability of teachers at SD Bendo Kapenewon, Samigaluh, Kulon Progo, using the Zoom Meeting application is still in the